PENGUATAN SKILL BERBAHASA INGGRIS STAF HOUSEKEEPING DI KEMBALI LAGI GUEST HOUSE - I Wayan Juniartha; Dewa Gede Bambang Erawan; Ni Ketut Mas Ayu Mayuni (LOKATARA SARASWATI, 2026)
This program was held at Kembali Lagi Guest House in Sanur, Bali, to improve the English skills of the housekeeping staff through demonstrations and direct practice methods. Based on observations, the housekeeping staff understood the basics of English but still had difficulty constructing sentences when speaking with guests, leading to misunderstandings. The program lasted for six weeks, with a sequence of programs including a pre-test, material, practice, and post-test. The material provided was relevant to situations often encountered by staff, including greeting and small talk with guests, giving simple directions, asking permission & explaining the cleaning schedule, offering breakfast information & other services, and handling guest complaints & responding to requests. The results of the course show that staff are more proficient in using vocabulary and sentence patterns, resulting in more effective communication with guests. Therefore, this course, with its methodology, has successfully improved the English skills of the housekeeping staff at Kembali Lagi Guest House.